Penggunaan Lingkaran Nama-Nama Hari untuk Meningkatkan Hasil Belajar Kognitif Matematika Kelas 1 SDABC Gunung Sitoli [The Use of the Names of the Days as a Teaching Aid to Increase Mathematics Cognitive Achievement of Grade 1 Students at ABC Elementary School in Gunungsitoli] - Beti Lamba; Widiastuti Widiastuti (Universitas Pelita Harapan, 2016)
The outcome of cognitive learning is a measurement of the students’ success during the learning process. The students’ learning outcome in putting the names of the days in order is considered in the low range. This is because the students misunderstood the concept of putting the names of the days in order and so the names of the days teaching aid is needed. The aim of this research is to improve the students’ cognitive learning outcomes using the names of the days teaching aid. The method of this research is Classroom Action Research (CAR) using four steps: planning, action, observation, and reflection, which is then analyzed using a descriptive analysis technique. The subject of this research is Grade 1 students of ABC Gunungsitoli elementary school. The instruments used in this research are observation sheet, check list, worksheet, student questionnaire sheet, mentor’s feedback sheet, reflection, and interview. Every cycle done is based on all the pre-planned lessons created by the researcher. According to the result of the research using the name of the days teaching aid, there were 26 students out of 28 students who improved their cognitive learning outcome by as much as 93%, which resulted in achieving the KKM standard (the standard is 65). This improvement was achieved by giving the students the names of the days teaching aid. Finally, it is concluded that using the names of the days teaching aid can improve the students’ learning outcomes in mathematic lessons in grade 1 at ABC elementary school in Gunungsitoli.BAHASA INDONESIA ABSTRAK: Hasil belajar kognitif merupakan suatu pengukuran untuk melihat keberhasilan siswa selama proses belajar. Hasil belajar mengurutkan nama-nama hari tentang sebelum dan sesudah, terbilang cukup rendah. Hal ini dikarenakan pemahaman konsep dari ilmu pengetahuan siswa yang salah dalam mengurutkan nama-nama hari. Oleh karenanya, dibutuhkan alat peraga lingkaran nama-nama hari. Penelitian ini bertujuan untuk meningkatkan hasil belajar kognitif siswa melalui penggunaan alat peraga lingkaran nama-nama hari. Penelitian dilakukan dengan menggunakan metode penelitian tindakan kelas menggunakan empat tahapan yaitu; perencanaan, tindakan, pengamatan, dan refleksi yang dianalisis secara deskriptif. Subyek penelitian ini adalah siswa kelas 1 SD yang dilakukan pada salah satu sekolah ABC Gunungsitoli. Penelitian ini menggunakan instrumen lembar observasi, lembar daftar cek (Check List), Lembar tes, lembar angket siswa, lembar umpan balik guru mentor, refleksi, dan wawancara. Setiap siklusnya dilakukan sesuai Rencana Pelaksanaan Pembelajaran (RPP). Berdasarkan hasil penelitian dengan menggunakan alat peraga lingkaran nama-nama hari, didapatkan 26 siswa dari 28 siswa hasil belajar kognitif meningkat yaitu 93% yang mencapai nilai standar KKM 65. Peningkatan tersebut dilakukan dengan cara memberikan alat peraga lingkaran nama-nama hari kepada setiap siswa. Dengan demikian dapat disimpulkan bahwa penggunaan alat peraga lingkaran nama-nama hari dapat meningkatkan hasil belajar kognitif pada mata pelajaran Matematika siswa kelas 1 SD ABC Gunungsitoli.